PENGARUH KEMUDAHAN, KUALITAS INFORMASI, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS LAZADA - Desy Wahyuni Angkat; Apriatni Endang Prihatini (Universitas Diponegoro, 2018)
Purchasing decisions are goals that every company should achieve. To be able to reach a high purchase decision, Lazada need to pay attention to ease, quality of information, and trust. This research aims to determine the effect of ease, quality of information, and trust in purchasing decisions partially or simultaneously. This type of research is explanatory research with 100 Lazada’s consumers by using purposive sampling technique and collected through the spread of questionnaires with Likert measurement scale. Data analysis method used is correlation, simple and multiple linear regression with SPSS 21 program. The results of this research indicate that ease, quality of information, and trust have a positive and significant effect on purchasing decisions partially or simultaneously. The trust variable has a greater influence than the others variable. From this research can be concluded that consumer perceptions of ease, quality of information, and trust are good. Meanwhile, purchasing decisions on Lazada is quite good. Thus, companies are advised to keep improving consumer purchasing decisions with giving more practically ease, better quality of information, and increased trust,that will improve purchasing decisions.